Relationship of Participants' Perceptions of the Material and Its Activities Following the Al-Ihsan Taklim Assembly in Katimahar, Pasaman Regency - Martika Yunerti; Vevi Sunarti (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
This research was motivated by the low activity of participants in attending al-ihsan taklim assembly activities in Katmahar, Pasaman Regency. This is caused by the lack of participant perceptions of the material given by the cleric at the taklim al-ihsan assembly in Katimahar, Pasaman Regency. This study aims to explain the participants 'perceptions of the taklim assembly material, describe the activeness of taklim assembly participants, and see the relationship between the members' perceptions about the taklim assembly material and its activeness in the implementation of the al-ihsan taklim assembly in Katimahar, Pasaman Regency. This type of research is quantitative correlational type. The study population was all registered members who were still active in the al-ihsan taklim assembly in katimahar, pasaman district, which numbered 50 people. Respondents in this study were 30 people. Then to determine the respondent used a random sampling technique, meaning that sampling is done randomly. Many of the samples taken were 60% of the total population of 30 people. The data collection technique used in this study was a questionnaire, while the data collection tool was a questionnaire. Data analysis techniques using the percentage formula and product moment. The results of this study indicate (1) the perception of participants of taklim al-ihsan assembly is less positive towards the material, (2) the activeness of participants in participating in the low taklim assembly starting from physical activeness, sensory activeness and spiritual activeness, and (3) there is a significant relationship between perception participants on the material with their activities following the al-ihsan taklim assembly in Katimahar, Pasaman Regency.Keywords: Perception, Learning Material, Activeness